PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP MINAT DAN HASIL BELAJAR KIMIA SISWA - Ghea Sefriza Pratiwi; Amrul Bahar; Rina Elvia (University of Bengkulu, 2019)
The purpose of this study is to describe the comparison of Think Talk Write learning models and Creative Problem Solving learning models to the interests and learning outcomes of chemistry in basic chemical law material. This research was conducted in January-May 2019. The research conducted was a kind of quasi-experimental research. The population of this study was class X MIA, totaling 136 students in SMAN 8 Kota Bengkulu in the academic year 2018/2019. Sampling was carried out after the normality and homogeneity test, so the X MIA 2 class was selected using Think Talk Write and X MIA 3 models that used the Creative Problem Solving model with a total of 68. Analysis of the data used was mean, normality test, test homogeneity, interest questionnaire analysis, N-Gain Score test and hypothesis test (t test). In general, both of these learning models are able to increase students 'interest and learning outcomes of chemistry, where the percentage of students' interest in learning chemistry in the Think Talk Write model is 80.5% and categorized as good, for the class of Creative Problem Solving model the percentage is 76.6% and also categorized as good. For the value of N-Gain score on Think Talk Write (TTW) class is and categorized as high while in the Creative Problem Solving class is 0.62 and is categorized as medium. The t-test results on the affective aspects are sig. (2-tailed) of 0.015 and on the cognitive aspect of 0.001. It states that there are significant differences in the interest and learning outcomes of chemistry that apply the Think Talk Write (TTW) learning model and Creative Problem Solving